Relationship between Islam and democracy in Dr. Mahathir Mohamad’s thought - Jaf, Dana Nawzar Ali (2014)
The purpose of this thesis is to determine, analyze and evaluate Dr. Mahathir Mohamad’s worldview on Islam, Islam’s role in public life and Islam’s relationship with democracy. This study has adopted a qualitative research design. Content analysis and interview are used as the main data collection methods. The study has academic significance as a contribution to the knowledge in the field of Islam and democracy debate. It also has practical significance for policy makers by presenting ideas of a Muslim statesman on matters related to religion and governance. This study has identified a scheme, good governance, in which Dr. Mahathir brings Islam and democracy together. Democracy defined as the process of choosing leaders through elections is a tool by which good citizens elect good governors, and Islam provides the systems of values which guarantees emergence of good citizens, governors and regulations.